Life's sweetest moments : simple, stunning recipes and their heartwarming stories - Ansel, Dominique (Chef) (Harvest, an imprint of William Morrow, 2024)
"From legendary and award-winning pastry chef Dominique Ansel, a baking book of more than 40 simple dessert recipes paired with heartwarming stories celebrating life's sweetest moments"--